Evaluating p97 Inhibitor Analogues for Potency against p97–p37 and p97–Npl4–Ufd1 Complexes. (4th April 2016) - Gui, Lin; Zhang, Xiaoyi; Li, Kelin; Frankowski, Kevin J.; Li, Shan; Wong, Daniel E.; Moen, Derek R.; Porubsky, Patrick R.; Lin, Henry J.; Schoenen, Frank J.; Chou, Tsui‐Fen
Abstract: We previously found that the p97 cofactor, p47, significantly decreased the potency of some ATP‐competitive p97 inhibitors such as ML240 [2‐(2‐amino‐1 H ‐benzo[ d ]imidazol‐1‐yl)‐ N ‐benzyl‐8‐methoxyquinazolin‐4‐amine] and ML241 [2‐(2 H ‐benzo[ b ][1, 4]oxazin‐4(3 H )‐yl)‐ N ‐benzyl‐5, 6, 7, 8 tetrahydroquinazolin‐4‐amine]. In this study, we aimed to evaluate inhibitor potencies against two additional p97 cofactor complexes, p97–p37 and p97–Npl4–Ufd1. We focused on these two cofactor complexes, because the protein sequence of p37 is 50 % identical to that of p47, and the Npl4–Ufd1 heterodimer (NU) is the most‐studied p97 cofactor complex. We screened 200 p97 inhibitor analogues for their ability to inhibit the ATPase activity of p97 alone and of p97–p37 and p97–NU complexes. In contrast to the effect of p47, p37 and NU did not significantly change the potencies of most of the compounds. These results highlight differences among p97 cofactors in influencing p97 conformation and effects of inhibitors on p97 complexes, as compared to p97 alone. Continued efforts are needed to advance the development of complex‐specific p97 inhibitors. Abstract : Complex situations : Targeting p97, a key player in the ubiquitin–proteasome system, is a promising emerging therapeutic strategy for cancer. Here, a structure–activity relationship (SAR) study of 200 p97/VCP inhibitor analogues for the p97–p37 and p97–Npl4–Ufd1 complexes was conducted. The results provide potential starting points for the development of p97‐cofactor complex‐specific inhibitors.